Genetic polymorphism of HLA-DRB1 alleles in Mexican mestizo patients with abdominal aortic aneurysms - Javier E. Anaya-Ayala; Susana Hernandez-Doño; Monica Escamilla-Tilch; Jose Marquez-Garcia; Kemberly Hernandez-Sotelo; Rodrigo Lozano-Corona; Daniela Ruiz-Gomez; Julio Granados; Carlos A. Hinojosa (BMC, 2019)
Abstract Background Multiple factors are implicated in the etiology and pathogenesis of Abdominal Aortic Aneurysms (AAA). Available literature of genetic studies has previously suggested the possible roles of autoimmunity, genetic predisposition and ethnic susceptibility. Due to the association with autoimmune diseases and proven application in population genetics, we aimed to investigate alleles of the Class II Human Leukocyte Antigens (HLA-DRB1) in the Mexican Mestizo population with aortic aneurysms and determine possible associations with susceptibility. Methods We performed a case Control Study; the HLA molecular typing was completed for DRB1 loci by LabType Sequence-Specific Oligonucleotide (SSO) SSO-OneLambda kit (Applied Biosystems; Thermo Fisher Scientific. Inc.) in the studied individuals. Allele frequencies (af) were determined, associations were assessed by chi square or fisher exact tests at significance level (< 0.05), and Odds Ratios (OR) were calculated using the STATA software version 14. Results The genetic polymorphism of HLA-DRB1 of fifty one patients (70% males with a mean age of 71 years) with atherosclerotic or also known as degenerative AAA were compared with 99 unrelated patients (60% males, mean age 65 years) without the disease [Control group (CG)] from the same ethnic group. We examined a total of 102 Class II HLA-DRB1 alleles of AAA patients and 198 from CG. When comparing af, we observed the HLA-DRB1*01 af of 0.139 in the AAA compared to 0.05 in the CG [p = 0.015, OR 3, 95% confidence interval (CI) 1.29-7.08], the HLA-DRB1*16 af were 0.109 in the AAA and 0.025 in CG (p = 0.006, OR 4.7, 95% CI 1.59-13.98). Conclusions Our study confirmed increased frequencies of the alleles HLA-DRB1*01 and HLA-DRB1*16 and their association to the development of AAA in Mexican Mestizo patients. The utility of genetic testing may assist in identifying individuals at genetic risk for the development of this disease in different ethnic groups, who might benefit from earlier ultrasound screening and closer imaging surveillance.